Pemetaan Rantai Pasokan Bawang dan Identifikasi Penyebab Kenaikan Harga Bawang Putih : Studi di Wilayah Yogyakarta - , GIGIH GINANJAR SAPUTRO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of the research is to discover garlic supply chain mapping and identify the cause of garlic price hikes between March to June 2013. The research take place in Yogyakarta garlic fields to identify garlic farmers role, distributor, retailer, and final customers. Identification process is achieved with qualitative research and explorative study, data is collected from in-depth interviews with respondents which was determined by Purposive Sampling and Snowball Sampling. Interview results are analyzed with Content Analysis and coding to generate a theme that serves the cause of garlic price rising occured. Based on data analyzing, there are six causes of garlic price hikes, including scarcity which is the effect of low garlic farmer commodity amount and low import supplies, import policies, extreme weather causing crop failure in Indonesia and importing countries, plague, cartel existence, and BBM price issues. These six causes are signed into Fishbone Diagram to identify the minor cause on each major cause of garlic price rising in Yogyakarta. With this identification model, it is served to evaluate the garlic supply chain process, hoping that garlic price rising will not exist in the future.